Cloud Backlash: Digital Sex Crimes and Anti-Feminism in South Korea - Schwartz, Anat (Atlantis, 2025)
This article explores the ongoing issue of bodily security, surveillance, and safety in and around South Korean digital spaces. By focusing on the Nth Room in March 2020, I argue that the rapid growth of digital and cloud-based technologies exacerbates social and political issues in Korea. I use an interdisciplinary methodological approach to critical gender and sexuality studies, data feminism, and Korean feminist scholarship to interrogate the relationship between transnational digital technologies, the deep-seated roots of patriarchy, and the contemporary anti-feminist backlash and conservative political landscape in South Korea. I argue that the cloud-based servers of instant messaging group chats pose a particular case that illustrates the challenges feminist activists face around digital sex crimes and surveillance in South Korea and transnationally.